Task Technology Fit: The Key to Digital Financial Management Generation X - Luh Putu Anggria Maeda Korry; Gusi Putu Lestara Permana (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This research aims to analyze how Task Technology Fit (TTF), financial literacy, and risk perception influence how Generation X manages their digital finances. The research also aims to address a gap in the existing literature, which has shown conflicting results regarding the role of TTF in financial technology adoption. Methodology: This research employed a quantitative approach using a questionnaire survey. The research was conducted in Badung Regency, with a total of 120 Generation X individuals selected via purposive sampling. Data analysis was performed using SPSS Version 25. Results: The results indicate that all three variables have a positive and significant influence. The TTF variable showed a significant positive effect, with a t-statistic of 3.586 (greater than the t-value of 1.980). Similarly, financial literacy had a strong positive influence, with a t-statistic of 7.620. Finally, risk perception also demonstrated a significant positive influence, with a t-statistic of 9.736. Conclusions: This study shows that Task Technology Fit, Financial Literacy, and Risk Perception have a positive effect on digital financial management among Generation X in Badung Regency, contributing 16.7%, while the remaining influence comes from factors outside the research model. Limitations: The study has several limitations, including a sample size restricted to Generation X in Badung Regency and a focus on only three variables. Contribution: This study offers both a theoretical and practical contribution. Theoretically, it provides new empirical evidence on the influence of TTF on Generation X.